KAJIAN DINAMIKA KELOMPOK PEMBUDIDAYA IKAN “ANUNTO” DALAM PENERAPAN MODEL TEKNOLOGI INTEGRATED MULTITROPHIC AQUACULTURE (IMTA) DI KOTA SAMARINDA - Vedro Yeremia Bara; Gusti Haqiqiansyah; Erwiantono (Jurnal Pembangunan Perikanan dan Agribisnis, 2015)
The purposes of study were to describe : the characteristics of Anunto’s fish farmer members, the perceptions toward IMTA’s models, the role of extension officer, group dynamics and analyze the correlation of all variables.The sampling method applied was census method taken 28 respondents. The data process was based on Spearman rank correlation test and presented descriptively. The results showed that members of Anunto group of fish farmers were dominated by productive ages, middle level on formal education, low level on non formal education, low level on experiences about aquaculture business, primary income sources were not related to fisheries. Group member perceptions toward IMTA characteristics were in the medium level consisting indicators of compatibility, complexity, triability and observability, while the indicator of relative advantage was high.The influence of extension officer in developing the group dynamics were high as facilitators and educators, while the influence as advocator was in medium level. Statistical analysis showed that group dynamic characteristic variables on indicators : aquaculture’s experience, joining group’s experience and primary income source were correlated toward the group dynamic variables on indicator : group’s purpose, group’s structure, group’s cohesiveness, groups’s task function and hidden agenda. The variable of member perception of technology on indicators: complexity and trialibility were correlated toward the group dynamic’s variable on indicator: group’s purpose and groups’s task function. The variable of extension officer’s influence on indicator:: advocator was correlated toward the group dynamic’s variable on indicator : group’s atmosphere.